Adverse events and nursing diagnosis in patients undergoing hematopoietic stem cell transplantation (Research, Society and Development, 2020)
The aim of this study was to describe the adverse events presented by patients on the day of infusion of hematopoietic progenitor cells and to identify corresponding nursing diagnosis. Prospective cross-sectional study, whose sample consisted of 62 patients who underwent hematopoietic stem cell transplantation (allogeneic and autologous). After ethical approval, data collection took place over a period of 16 months in a public hospital in the state of São Paulo. About 53% of the transplant recipients were male, 54.8% had at least one comorbidity and 61.3% underwent allogeneic transplantation. For each type of adverse event (by organic system) presented, at least one nursing diagnosis was indicated, totaling 26 diagnosis and the most frequent ones were "risk of bleeding", "risk of allergic response", "fatigue" and "risk of impaired cardiovascular function". The highest frequency of elected nursing diagnosis belonged to the “security / protection” domain (n = 11), followed by the “activity / rest” domain (n = 5). This study found a higher frequency of nursing diagnosis belonging to the safety/protection domain and the activity/rest domain, which can be a reference for nurses in planning nursing care, with a view to the quality of care and the safety of onco-hematological patients.